Taxonomic Notes on Microcos (Malvaceae-Grewioideae) in India - Nandikar, Mayur D.; Janarthanam, M.k. (Phytotaxa, 2016)
In India, the delimitation and taxonomic status of the genus Microcos has historically been in a state of flux. While revising the genus Grewia for India, authors found certain taxonomic and nomenclatural inconsistencies in the Floras while treating M. paniculata and M. calophylla. The aims of the present study are to resolve these inconsistency, to review the genus Microcos in India, and the lectotypification of M. calophylla (≡ Grewia calophylla).